Implementasi Metode Agile pada Sistem Informasi Penggajian Berbasis Web di Perusahaan - Muhammad Faittullah Akbar Akbar; Dede Firmansyah Saefudin (LPPM UBSI Kampus Kota Tegal, 2026)
This study aims to implement the Agile method in developing a web-based employee Payroll information system to improve efficiency, accuracy, and transparency in Payroll processes within a company. The main problem identified is that Payroll processing is still carried out manually, which may lead to calculation errors, delays, and lack of control in the approval process. The Agile method is chosen due to its iterative and flexible approach, allowing system development to be conducted in stages based on user requirements. The system is developed using the Laravel framework and MySQL database, featuring employee data management, attendance tracking, automated Payroll calculation, role-based access control, and a multi-level approval system. The results show that the developed system improves Payroll efficiency, reduces calculation errors, and enhances data security and transparency. Furthermore, the system enables users to access Payroll information in real time. Therefore, the implementation of the Agile method is proven to be effective in supporting Payroll management systems.